2008
DOI: 10.1159/000178814
|View full text |Cite
|
Sign up to set email alerts
|

Fasudil Hydrochloride Hydrate, a Rho-Kinase Inhibitor, Suppresses 5-Hydroxytryptamine-Induced Pulmonary Artery Smooth Muscle Cell Proliferation via JNK and ERK1/2 Pathway

Abstract: Excessive proliferation of pulmonary artery smooth muscle cells (PASMCs) plays a critical role in the development of pulmonary artery hypertension, and inhibition of PASMC proliferation has been shown to be beneficial to patients with this disease. Recent studies indicate that Rho/ROCK is critically involved in the proliferation of smooth muscle cells. However, the signal transduction of Rho/ROCK and its downstream signaling are not fully understood. In the present study, we investigated the antiproliferation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 61 publications
5
15
0
Order By: Relevance
“…58 Fasudil inhibits VSMC proliferation by blocking the nuclear translocation of ERK1/2. 59 All of these reports support our present study finding that treatment with fasudil inhibited the phosphorylation of Rho-kinase and ERK1/2. In contrast, sildenafil inhibits VSMC proliferation through activating the cGMP/PKG pathway, where cGMP activates PKG to induce the mitogen-activated protein kinase phosphatase-1 (MKP-1) enzyme that deactivates ERK1/2.…”
Section: Additive and Synergistic Effects Of The Combination Therapysupporting
confidence: 90%
“…58 Fasudil inhibits VSMC proliferation by blocking the nuclear translocation of ERK1/2. 59 All of these reports support our present study finding that treatment with fasudil inhibited the phosphorylation of Rho-kinase and ERK1/2. In contrast, sildenafil inhibits VSMC proliferation through activating the cGMP/PKG pathway, where cGMP activates PKG to induce the mitogen-activated protein kinase phosphatase-1 (MKP-1) enzyme that deactivates ERK1/2.…”
Section: Additive and Synergistic Effects Of The Combination Therapysupporting
confidence: 90%
“…This seems to be because of a side-effect of the inhibitor in the epidermis, namely the concomitant inhibition of Rok signaling and ERK phosphorylation ( Supplementary Fig. S8B), sporadically observed in other tissues (25)(26)(27). ERK inhibition by Fasudil is not observed in the forestomach (Fig.…”
Section: A B Cmentioning
confidence: 95%
“…It has been suggested that ROCK1 plays a key role in pathological fibrosis of the organs, whereas ROCK2 is related to organ hypertrophy (23,24). Other studies found that ROCK not only increases the polymerization of the actin cytoskeleton, but also induces the expression of fibrosis-related genes and proteins (19,23,25,26). Phrommintikul et al (23) confirmed in the animal model of stress-induced cardiac hypertrophy that the ROCK inhibitor reduces the synthesis of cardiac collagen, and improves the diastolic function.…”
Section: Introductionmentioning
confidence: 99%